PENGARUH LIKUIDITAS, PROFITABILITAS, SOLVABILITAS, DAN STRUKTUR AKTIVA TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2016) - Arinda Norvatimah, 13.05.51.0232; Irsad, Moch. (Students' Journal of Economic and Management, 2018)
This study aims to examine the effect of liquidity, profitability, solvency, and asset structure on stock prices on manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2016 period. The sampling method uses purposive sampling with the study period of 2014 to 2016. The relationship and or influence between variables is explained by using multiple linear regression analysis method. The results showed that liquidity, profitability, solvency, and asset structure simultaneously affect the stock price. Liquidity and asset structure have a positive and insignificant effect, profitability has a positive and significant effect, while solvency has a negative and insignificant effect. Keywords: liquidity (CR), profitability (ROE), solvency (DER), asset structure (SA), stock price